Paraphilia Exhibitionism between Sharia and Law: A Comparative Analysis - Islamul Haq; M Ali Rusdi Bedong; Abdul Syatar; Muhammad Majdy Amiruddin (Al-'Adl, 2021)
Paraphilia exhibitionism is a form of sexual disorder and immoral offences. This study aims to compare the status of perpetrators of exhibitionism in positive law and Islamic law. This research is qualitative research that uses literature studies. The results showed similarities between Islamic law and positive law on the classification of exhibitionism as a crime. Islamic law and positive law are also similar in terms of ensnaring perpetrators of exhibitionism as someone who can be held accountable. The criminalization aspect of positive law includes exhibitionism as a complaint deliberation. While in Islamic criminal law categorizes the crime of exhibitionism as ordinary deliberation.